Los juegos didácticos utilizados por los docentes y el aprendizaje de las niñas y niños de 3 a 4 años de edad del centro de educación inicial Dirigentes del Futuro de la parroquia Malacatos, período lectivo 2013-2014. Lineamientos alternativos - Riofrio Escobar, Viviana del Cisne (2015)
The present investigation pertains to the teaching GAMES USED BY THE TEACHERS AND THE LEARNING OF THE GIRLS AND CHILDREN FROM 3 TO 4 YEARS OF AGE OF THE CENTER FOR EARLY CHILDHOOD EDUCATION LEADERS OF THE FUTURE OF THE PARISH MALACATOS, ACADEMIC PERIOD 2013-2014. ALTERNATIVE GUIDELINES. To develop the present investigation was made as a General Objective: To determine the use of educational games for the development of the children's learning and girls from 3 to 4 years of age the center of Initial Education leaders of the future of the Parish Malacatos in the period 2013-2014. The research is based on a non-experimental design, therefore followed the logical route that allowed problematize the reality, to describe the information, verify the objectives and establish the respective conclusions and recommendations. The methods used were the scientist, the inductive, the bibliography, the analytical and statistical, within the techniques employed were the survey to the teachers and the observation guide for girls and children. Working with a population of 60 children and 3 teachers. After obtaining the results with the implementation of the above-mentioned instruments, he came to the conclusion that: The 3 teachers that represent the 100% consider that sometimes use and apply different kinds of educational games, and that they consider that these are important during the learning process, and that to not use them in education, does not allow the achievement of better results in the teaching-learning process of boys and girls from 3 to 4 years of the Center for Early Education leaders of the future of the Parish Malacatos. From the observation guide applied to girls and boys in a minimum percentage of 60% presented difficulties at the time of school learning in different areas, and in some classes showed little interest at the time of carrying out the activities listed by the teachers, the same as in a limited way were applied on different kinds of games as teaching school motivation. It is therefore recommended that: The teachers of the school plan, implement and organize workshops of didactic games aimed at children, by applying different techniques and methods in activities according to the characteristics of each game, and in addition must use everything you need in the related teaching material, for the implementation of the activities, either within the classroom or in the open air to encourage the learning process. In addition the teachers must take special care with the boys and girls, who have learning problems, and encouraging them to continue with the implementation of the alternative guidelines with different kinds of games that i has enabled it to develop and propose.